Geometry Learning Media Application For Elementary School Students Using Android-Based Augmented Reality Technology - Sutarman; Rian Luthfi Fadilah (The Indonesian Journal of Computer Science, 2023)
Geometry is one of the subject matter in mathematics. Geometry has many type of shape, formula, area and volume. So there are many elementary school students feel no interest in studying geometry material because they feel difficult and don't understand it properly it is clear what each of these geometry looks like. To meet these demands, in line with developments in science and technology, the use of learning media is a solution. Increasingly diverse and interactive technology, one of which comes with utilizing AR technology. The use of augmented reality which is able to present 3D objects in visualizing geometric grids can make it easier to remember geometric shapes and utilizing this technology is able to create learning applications that stimulate students interest in learning to carry out learning activities actively and independently